1975
DOI: 10.1037/0096-1523.1.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of attention and the locus of adaptation tp displaced vision.

Abstract: Experimental subjects were exposed to prism-induced visual displacement of a target whose location was correctly given by proprioceptive-kinesthetic information. Control subjects were exposed alternately to visual displacement or proprioceptive-kinesthetic location information. During the adaptation period, experimental subjects in the visual attention condition performed a localization task that directed them to attend selectively to the visual modality; experimental subjects in the proprioceptive attention c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 14 publications
6
59
0
1
Order By: Relevance
“…Welch and Warren (1980), in their model of crossmodal bias, distinguish between deployment of attention based on modality appropriateness (primary attention), a notion proposed by Posner et al (1976), and that based on instructional and contextual variables that are under the control of the experimenter (secondary attention). The results of studies on both the visual -auditory conflict (Canon 1970;Radeau 1974) and the visual -proprioceptive conflict (Kelso et al 1975) are consistent with the notion that allocation of secondary attention is not immutable and can be experimentally manipulated. Temporally shifting the distribution of attention between the conflicting modalities resulted in a reduction of the size of recalibration in the modality when attention was focused on it, relative to when attention was focused on the other modality.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Welch and Warren (1980), in their model of crossmodal bias, distinguish between deployment of attention based on modality appropriateness (primary attention), a notion proposed by Posner et al (1976), and that based on instructional and contextual variables that are under the control of the experimenter (secondary attention). The results of studies on both the visual -auditory conflict (Canon 1970;Radeau 1974) and the visual -proprioceptive conflict (Kelso et al 1975) are consistent with the notion that allocation of secondary attention is not immutable and can be experimentally manipulated. Temporally shifting the distribution of attention between the conflicting modalities resulted in a reduction of the size of recalibration in the modality when attention was focused on it, relative to when attention was focused on the other modality.…”
Section: Introductionsupporting
confidence: 77%
“…However, in both studies instructions were very different from those used by Canon (1970), Kelso et al (1975), and Radeau (1974). Warren and Schmitt (1978) and Warren (1979) informed subjects that their vision was prismatically displaced and therefore unreliable.…”
Section: Introductionmentioning
confidence: 99%
“…To account for a functional equivalence between mental images and actual pointing errors at peripheral levels, this model might propose that images of pointing errors, like observed pointing errors, can be compared directly with motor commands. According to an alternative model, changes in visual-motor coordination specific to peripheral levels occur when the observed positions of the pointing arm are compared with its felt positions during adaptation procedures (Harris, 1965;Kelso et al, 1975;Mather & Lackner, 1977). To account for a functional equivalence between mental images and actual pointing errors at peripheral levels, this model might propose that mental images of pointing errors, like observed errors, can lead to changes in how proprioceptive information is processed.…”
Section: Discussionmentioning
confidence: 99%
“…First, the task of imagining pointing errors is greatly simplified in that subjects need to form only a single mental image corresponding to each pointing error. Secondly, previous studies have shown that pointing changes that result when subjects are merely told, upon completion of movement, the location of their unseen pointing errors are similar to those changes that result when the same errors are acturally observed (Kelso, Cook, Olson, & Epstein, 1975;Uhlarik, 1973). While such changes may result solely from verbal descriptions of pointing errors, they could also result from mental images of pointing errors constructed spontaneously by subjects in response to these descriptions.…”
mentioning
confidence: 92%
“…Proprioceptive aftereffects are predominant when sight of the pointing hand during exposure occurs early in the pointing movement, while visual aftereffects predominate when such visual feedback is delayed until near the terminus of the pointing movement (Canon, 1970;Cohen, 1967;Kelso, Cook, Olson, & Epstein, 1975;Redding & Wallace, 1990, 1994, 2000Uhlarik, 1973;Uhlarik & Canon, 1971). Proprioceptive aftereffects are also larger when the rate of pointing during exposure is high, while visual aftereffects are larger with low-exposure pointing rates Redding & Wallace, 1990, 1994.…”
mentioning
confidence: 99%